Diabetes systems biology : quantitative methods for understanding beta-cell dynamics and function - Khadra, Anmar, 1974- (Biophysical Society-IOP series., 2020)
Diabetes Systems Biology provides senior undergraduate students and junior scientists, interested in diabetes systems biology, with a tool to learn more about the mathematical models and methods used to understand macroscopically and microscopically beta-cell behaviour in health and disease. The book introduces readers to the quantitative methods used to examine beta-cell dynamics, islet biology and architecture, as well as diabetes etiology and implications. The goal is to allow junior researchers in the fields of mathematical biology and biophysics to obtain a broad understanding of these quantitative methods, and guide them into taking the first steps into the field of diabetes systems biology. At the end of each chapter, several problem-solving exercises (that require both analytical and computational skills) are provided for the readers to help them become more proficient in this field. Part of Biophysical Society-IOP series.